An Experimental Evaluation of Combination of Features on the IPNoSys - Cruz, Marcos Oliveira da; Kreutz, Márcio Eduardo; Araújo, Sílvio Roberto Fernandes de (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Routing algorithms are an important aspect to be considered in design and development of networks-on-chip for having a direct impact on the system performance. As part of its processing environment, a good routing algorithm aim is to provide a rational and optimized use of system resources and also prevent problems such as deadlock, livelock and starvation. The network-on-chip IPNoSys was designed to provide computing resources in order to allow the exploitation of packet-level parallelism. A good distribution of packets through the paths of the network is important to allow a good exploitation of its resources. This paper presents two routing algorithms for IPNoSys, namely, its original algorithm named Spiral complement and an alternative algorithm called Zig-zag. Tests were run in order to evaluate the combination of a routing algorithm with a specific number of virtual channels and packet-level parallelism exploitation.